Climate models without preindustrial volcanic forcing underestimate historical ocean thermal expansion. Issue 8 (23rd April 2013) - Gregory, J.M.; Bi, D.; Collier, M.A.; Dix, M.R.; Hirst, A.C.; Hu, A.; Huber, M.; Knutti, R.; Marsland, S.J.; Meinshausen, M.; Rashid, H.A.; Rotstayn, L.D.; et al.
<x xml:space="preserve">Abstract</x> [1] Episodic explosive volcanic eruptions are a natural part of the climate system but are often omitted from atmosphere‐ocean general circulation model (AOGCM) preindustrial spin‐up and control experiments. This omission imposes a negative bias on ocean heat uptake in simulations of the historical period. In models of a range of complexity, we find that global‐mean sea level rise due to thermal expansion during the last ∼ 150 years is consequently underestimated by 5–30 mm, which is a substantial proportion of the model mean of 50 mm in Coupled Model Intercomparison Project Phase 3 AOGCMs with anthropogenic forcing only, and is therefore important in accounting for 20th century sea level rise. We test and recommend a procedure for removing the bias.